Introducing research in early childhood - Bolshaw, Polly; Josephidou, Jo (London : SAGE Publications Ltd, 2019)
'What a useful book for the beginner researcher! Offering a grounding in the different kinds of research conducted in the field of early childhood, this book's inviting and accessible style will support the novice researcher, and the development of criticality in relation to research.' Deborah Albon, Senior Lecturer in Early Childhood Studies, University of Roehampton What does the term'research' in early childhood actually mean? What does research involve, and how do you go about doing it? This book explains exactly what'research' is; it explores key ideas, themes and terminology to provide you with a clear understanding of its importance to your early years or early childhood studies degree. It will help you: Understand what it means to think critically, and unpick childhood research Learn how to analyse, examine and understand the importance of others' research Get to know how research is designed and carried out Appreciate the importance of ethics Get to grips with translating research into real life in an early childhood setting. Laying the foundations to develop your confidence in talking about research and making links between theory and practice, this book will support you as you begin your research journey into the world of early years. Polly Bolshaw is a Senior Lecturer in Early Childhood Studies at Canterbury Christ Church University. Jo Josephidou is a Senior Lecturer in Early Childhood Studies at Canterbury Christ Church University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Child development -- Research; Children -- Research